Short communication: Detection of antibiotic resistance, mecA, and virulence genes in coagulase-negative Staphylococcus spp. from buffalo milk and the milking environment - Pizauro, Lucas J.L. [UNESP]; de Almeida, Camila C. [UNESP]; Soltes, Glenn A.; Slavic, Durda; de Ávila, Fernando A. [UNESP]; Zafalon, Luiz F.; MacInnes, Janet I. (American Dairy Science Association, 2019)
The aim of this study was to determinate whether coagulase-negative staphylococci (CNS) from buffalo milk or the milking environment possess virulence factors that are associated with intramammary infections or antimicrobial resistance. Milk samples (n = 320) from 80 lactating buffalo were evaluated for clinical and subclinical mastitis by physical examination, the strip cup test, California Mastitis Test (CMT), and somatic cell count (SCC) over a 4-mo period. In addition, swabs were obtained from the hands of consenting milkers (16), liners (64), and from the mouths (15) and nostrils (15) of buffalo calves. No clinical cases of mastitis were observed; however, CMT together with SCC results indicated that 8 animals had subclinical mastitis. Eighty-four CNS isolates were identified by MALDI-TOF MS and cydB real-time PCR (qPCR) and then evaluated by qPCR for presence of the eta, etb, sea, sec, cna, seb, sei, seq, sem, seg, see, and tst toxin genes, adhesion- and biofilm-associated genes (eno, ebps, fib, fnbA, coa), and the methicillin resistance gene (mecA). Resistance to antibiotics commonly used for mastitis treatment in Brazil was determined using the Kirby-Bauer test. Two strains were positive for the see and eta toxin genes; and mecA (1), eno (27), ebps (10), fnbA (10), and coa (5) genes were also detected. A notable number of isolates were resistant to erythromycin (30), penicillin (26), and cotrimoxazole (18); importantly, 10 vancomycin-resistant isolates were also detected. A smaller number of isolates were resistant to rifampicin (8), oxacillin (7), clindamycin (5), cefepime (4), tetracycline (3), ciprofloxacin (2), and chloramphenicol (1), and none were resistant to gentamicin or ciprofloxacin. Isolates with resistance to 2 (13 isolates), 3 (3), 4 (3), 5 (1), and 6 (1) antibiotics were detected. Taken together, our findings suggest that CNS isolates may not be a significant cause of clinical or even subclinical mastitis in buffaloes, but they may be a reservoir of virulence and antibiotic resistance genes.
Keywords: antibiotic resistance; biofilm; dairy buffalo; virulence genes